ChemInform Abstract: Studies on Substituted Benzo[h]quinazolines, Benzo[g]indazoles, Pyrazoles, 2, 6‐Diarylpyridines as Antitubercular Agents. Issue 13 (1st April 2014) - Maurya, Hardesh K.; Verma, Ruby; Alam, Saba; Pandey, Shweta; Pathak, Vinay; Sharma, Sandeep; Srivastava, Kishore K.; Negi, Arvind S.; Gupta, Atul
Abstract All synthesized compounds are screened for their in vitro antitubercular activity against Mycobacterium tuberculosis H37Rv strain.